Heavy Metal Free Nanocrystals with Near Infrared Emission Applying in Luminescent Solar Concentrator. Issue 6 (26th May 2017) - Chen, Wei; Li, Jiagen; Liu, Peizhao; Liu, Haochen; Xia, Jiuxu; Li, Shang; Wang, Dan; Wu, Dan; Lu, Wei; Sun, Xiao Wei; Wang, Kai
Abstract : Low reabsorption, near infrared (NIR) emission, and heavy metal free are key trends for the nanocrystals (NCs) based luminescent solar concentrator (LSC). In this research, heavy metal free AgInS2 /ZnS (AIS/ZnS) NCs have been synthesized and utilized by LSC technique with NIR emission for the first time. The AIS/ZnS demonstrated a tetragonal crystal phase and an NIR emission at 918 nm when the ratio of [Ag]:[In] = 1: 0.5 for metal elements in precursors. The quantum efficiency was also improved to 60.3% as the absolute quantum yield (QY) after inorganic surface passivation. Moreover, AIS/ZnS LSCs have been fabricated by in situ polymerization. Benefiting from low reabsorption by "large effective Stokes shift" and high emission efficiencies of the AIS/ZnS NCs, the optical power efficiency (OPE) of large area AIS/ZnS LSC reached to 3.94%, and interestingly, the LSC also revealed high color transmittance in the visible range, which could maintain high quality of the transmitted natural light with color rendering properties at above 97 for Ra, and correlated color temperature of around 4500 K. These NCs and related LSCs will play an important role in smart building integrated photovoltaics. Abstract : By tuning the ratio of [Ag]:[In] = 1:0.5 in raw materials, AgInS2 /ZnS nanocrystals with near infrared emission have been synthesized and introduced to luminescent solar concentrators (LSCs). We have not only investigated the optical power efficiency of LSCs, but also evaluated the quality of the transmitted light.